2002
DOI: 10.1590/s1516-89132002000100010
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Structure and Taxonomy of Petunia and Calibrachoa (Solanaceae)

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
0
9
0
2
Order By: Relevance
“…Glandular trichomes are common among the other clades in asterids as well. For example, Solanaceae short stalked globular trichomes (Type VI) that secrete defensive proteins (Shepherd et al, 2005) and other secondary metabolites are also structurally similar to the asterid salt glands with respect to the cellular organization of a basal cell, 1–2 stalk cells, and a few secretory cells on top (Reis et al, 2002; Glas et al, 2012; Munien et al, 2015). …”
Section: Salt Glands Have Evolved Independently Many Timesmentioning
confidence: 99%
“…Glandular trichomes are common among the other clades in asterids as well. For example, Solanaceae short stalked globular trichomes (Type VI) that secrete defensive proteins (Shepherd et al, 2005) and other secondary metabolites are also structurally similar to the asterid salt glands with respect to the cellular organization of a basal cell, 1–2 stalk cells, and a few secretory cells on top (Reis et al, 2002; Glas et al, 2012; Munien et al, 2015). …”
Section: Salt Glands Have Evolved Independently Many Timesmentioning
confidence: 99%
“…The species of Petunia and Calibrachoa were generally considered to be part of the same genus until 1985. Wijsman (1982Wijsman ( , 1983 investigated the origin of the garden petunia by crossing different species and, based on these successful crosses, Wijsman & Jong (1985) concluded that the species should be classified into two different groups according to the chromosome numbers and certain morphological characters, such as leaf margins, aestivation, flower symmetry, calyx, anther colour and seed coats, and their classification is supported by cytotaxonomic, reproductive, anatomical and chemical studies (Ellinger et al, 1992;Stehmann et al, 1996;Watanabe et al, 1996a, b;Reis, Sajo & Stehmann, 2002).…”
Section: Vegetationmentioning
confidence: 99%
“…Trichomes—the term deriving from the Greek word “trichos”, which means hair—are, in most cases, not connected to the vascular system of the plant, but instead are extensions of the epidermis from which they originate [1]. Trichomes range in size from a few microns to several centimeters and they exhibit a tremendous species-specific diversity in shape (for examples, see [2]), and, therefore, they are often used as diagnostic characteristics for the identification of plant species, e.g., [3]. Trichomes are mainly found on leaves and stems, but they can also occur, depending on the species, on petals, petioles, peduncles and seeds [1].…”
Section: Introductionmentioning
confidence: 99%